2015
DOI: 10.1097/jto.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse High Intensity PD–L1 Staining in Thymic Epithelial Tumors

Abstract: Introduction Blockade of the immune checkpoint programmed death receptor ligand-1 (PD-L1)/PD-1 pathway has well-established clinical activity across many tumor types. PD-L1 protein expression by immunohistochemistry (IHC) is emerging as a predictive biomarker of response to these therapies. Here, we examine PD-L1 expression in a thymic epithelial tumor (TET) tissue microarray (TMA). Methods The TMA contained 69 TETs and 17 thymic controls, with each case represented by triplicate cores. The TMA was stained w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(141 citation statements)
references
References 44 publications
14
122
5
Order By: Relevance
“…In the current study, the PD-L1 clone EPR1161 [2], which recognizes the C-terminus extracellular domains of PD-L1, was employed. In contrast, previous reports studying PD-L1 in thymic epithelial tumors used clone 5H1, which targets extracellular domains of PD-L1, or E1L3N, which targets intracellular domains, respectively (22,23). These three studies (including ours) demonstrated slightly different populations of cases with high PD-L1 expression in thymic carcinoma (58.7%-80%), which may have resulted from the use of distinct antibodies and PD-L1 cut-off values.…”
Section: Discussioncontrasting
confidence: 42%
See 2 more Smart Citations
“…In the current study, the PD-L1 clone EPR1161 [2], which recognizes the C-terminus extracellular domains of PD-L1, was employed. In contrast, previous reports studying PD-L1 in thymic epithelial tumors used clone 5H1, which targets extracellular domains of PD-L1, or E1L3N, which targets intracellular domains, respectively (22,23). These three studies (including ours) demonstrated slightly different populations of cases with high PD-L1 expression in thymic carcinoma (58.7%-80%), which may have resulted from the use of distinct antibodies and PD-L1 cut-off values.…”
Section: Discussioncontrasting
confidence: 42%
“…Thus far, few studies have examined PD-L1 expression in thymic epithelial tumors (22)(23)(24). Confined to thymic carcinoma as a subset of thymic epithelial tumors, only one of these reports mentioned the prognostic role of PD-L1, finding that there was no difference in OS according to PD-L1 positivity (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…129 More recently, PD-L1 positivity has been detected in normal thymus tyissue, thymomas and thymic carcinomas, with an apparent differential distribution between histological grades. 130 131 whilst in the other study PD-L1 high expression was associated with worse OS. 130 Remarkably, in this same study PD-L1 high-expression lymphocytes were detected in 14.8% of TETs (8 of 54) and 29.4% of control samples (5 of 17), but no lymphocyte staining was observed in the other study.…”
Section: Pd-l1 Expression In Thymic Epithelial Tumorsmentioning
confidence: 92%
“…However, when data becomes available from ongoing systematic genomic analyses of TETs (i.e., The Cancer Genome Atlas), targeted therapies could be a more effective induction therapy in the right subset of TETs, although the 70-80% response rate achieved with chemotherapy will be difficult to surpass. In addition, with the recent detection of programmed-death receptorligand-1 in TETs (44), there may be a role for immunebased therapies, though development of this approach must be made with extreme caution given the high rates of autoimmune disease in patients with thymoma. We see the most important role for histological biopsies in advanced TETs for the exclusion of other malignancies rather than the identification of TET WHO subtype.…”
Section: The Importance Of 'Downstaging'mentioning
confidence: 99%